INOVASI PELAYANAN DALAM PENGURUSAN PAJAK KENDARAAN BERMOTOR PADA UPTD SAMSAT KOTA BUKITTINGGI - Ilham "; Harapan Tua R.F.S (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
UPTD SAMSAT Bukittinggi is the public services delivery unit in the motor vehicle tax administration, improve services UPTD SAMSAT In Bukittinggi innovation in the management of motor vehicle tax is to use SAMSAT kiosk machine. The purpose of this study was to determine how service innovation and determine the factors that affect service delivery innovations in the management of motor vehicle tax on UPTD SAMSAT Bukittinggi.This study uses the theory of Everett M. Rogers (2003) in Suwarno (2008: 17), In application of innovation have the attributes that are inherent in such innovations. Attributes innovation in question is as follows Relative Advantage, Compatibility), Complexity, Triability, observability. The method used is qualitative data collection through interviews, observation and documentation.These results indicate that innovation in public services in the management of motor vehicle tax on UPTD SAMSAT Bukittinggi is to use the machine kiosk SAMSAT greatly benefit the community, but much remains encountered obstacles like the community who can not operate a machine and not a serving officer operating the machine kiosk SAMSAT, other barriers such as broken network, and electricity shut off, so that people could not use the SAMSAT kiosk machine.Keywords: Innovation, Service, Motor Vehicle Tax